2002
DOI: 10.1007/s00468-002-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional groups in Quercus species derived from the analysis of pressure–volume curves

Abstract: Oaks that occupy Mediterranean phytoclimates share common leaf features (evergreenness, high leaf dry mass per unit area, LMA). Due to this phytoclimatic, morphological, and phenological convergence it has been suggested that they might constitute a coherent functional group. To confirm this hypothesis, some physiological parameters were determined after calculating pressure-volume curves (P-V curves) using the free-transpiration method. Seventeen Quercus species from contrasting phytoclimates were studied: si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
2
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 58 publications
11
112
2
11
Order By: Relevance
“…In oak species, drought commonly results in decreases in Ψπ 100 of about 0.6 MPa or less [2,3,6,13,14]. Decreases in osmotic potential near to 0.5 MPa under moderate drought conditions and differences in osmotic adjustment between seedlings grown under low light (LL1 and LL2) and high light (HL1 and HL2) environments of 40% demonstrated an osmotic adjustment capacity in accordance to water conditions in our study.…”
Section: (A) (B)supporting
confidence: 70%
See 1 more Smart Citation
“…In oak species, drought commonly results in decreases in Ψπ 100 of about 0.6 MPa or less [2,3,6,13,14]. Decreases in osmotic potential near to 0.5 MPa under moderate drought conditions and differences in osmotic adjustment between seedlings grown under low light (LL1 and LL2) and high light (HL1 and HL2) environments of 40% demonstrated an osmotic adjustment capacity in accordance to water conditions in our study.…”
Section: (A) (B)supporting
confidence: 70%
“…The result is a recruitment of seedlings of variable age, not more than 30 cm high, with a deep root system, that in most cases are not able to perform adequately, as long as favourable conditions for growth do not occur [29,54]. Thus, although mature cork oak is a shade-intolerant evergreen species, which shows a water-saver strategy under water stress [14,34,45], some canopy protection during the seedling state favours its establishment and early growth.…”
Section: Introductionmentioning
confidence: 99%
“…Q. ilex is a sclerophyllous Mediterranean oak more drought tolerant than Q. pyrenaica which has been classified as a nemoro-Mediterranean oak (Corcuera et al, 2002). P. pinaster is considered more drought tolerant than P. sylvestris.…”
Section: Study Region and Speciesmentioning
confidence: 99%
“…Parameters as A n,mx , B pot , T mx , k, ψ * , ψ w and I mx depend on the specie selected to be modelled. For vegetation in semiarid and arid environment, Corcuera et al (2002) reported 3.2 MPa wilting water potential ψ w as a point of turgor-loss, whereas used 3 MPa. The last one was used for the HORAS simulations.…”
Section: Parameters Estimationmentioning
confidence: 99%